If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(G)=4(G-5)+G2
We move all terms to the left:
(G)-(4(G-5)+G2)=0
We calculate terms in parentheses: -(4(G-5)+G2), so:We get rid of parentheses
4(G-5)+G2
We add all the numbers together, and all the variables
G^2+4(G-5)
We multiply parentheses
G^2+4G-20
Back to the equation:
-(G^2+4G-20)
-G^2+G-4G+20=0
We add all the numbers together, and all the variables
-1G^2-3G+20=0
a = -1; b = -3; c = +20;
Δ = b2-4ac
Δ = -32-4·(-1)·20
Δ = 89
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$G_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$G_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$G_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-\sqrt{89}}{2*-1}=\frac{3-\sqrt{89}}{-2} $$G_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+\sqrt{89}}{2*-1}=\frac{3+\sqrt{89}}{-2} $
| -9+2y=2y-9 | | 3n+12=-18 | | 3x-12=3(x-4 | | -9+8x=3+6x | | -3(1-1/3v)=-9 | | m-13=-27 | | 1.5x+45=105 | | 4(2p-1)=3(3p+4) | | 3x4+36x2+108=0 | | -57+5x=53 | | Y=-4.9x^2+9.8 | | 1/2=y/12=y | | 7(v-2)-5=-4(-6v+6)-7v | | 6x-65=19+9x | | y=-12^2+10 | | 3m+20=-m-20 | | 6p+4=4-2p | | 6(-8r-2)-3r=2r+6(8r-2) | | 1+10d=10d | | -3(1-1/3v)=9 | | 2x+1=-15+4x | | 3x-20+x+40=145 | | x+61=140 | | X+9=8x-6-9x | | 2x-5-7x=-14 | | 3x+(5-1)=-6x+(4-2) | | 5-m/8=10 | | 2m=8.72 | | 3x-5/2=5x-30/3 | | -7-b+11b=9b-20 | | 5.3+y=10 | | x+40+3x-20=145 |